Caustic ingestion: Has the role of the gastroenterologist burnt out?. (18th March 2019) - Gill, Madeleine; Tee, Derrick; Chinnaratha, Mohamed Asif
Abstract: Caustic ingestion is a frequent presentation to EDs and encompasses a wide range of injury to the gastrointestinal tract. Endoscopy has long been considered the gold standard of investigation, even in patients with low likelihood of severe injury, and informs the decision for emergency surgery. However, recent evidence suggests that computed tomography (CT) scan can accurately diagnose digestive tract necrosis and, more importantly, guide towards more judicious use of surgical management, with improved mortality and digestive autonomy. CT scan also accurately predicts risk of stricture formation. We propose an algorithm for the use of CT scan, rather than endoscopy, as the first‐line investigation in the assessment of caustic ingestion.